Emergent life events in the delivery of a caregiver-mediated evidence-based intervention for children with autism spectrum disorder in publicly funded mental health services. (July 2020) - Lind, Teresa; Lau, Anna S; Gomez, Christopher; Rodriguez, Adriana; Guan, Karen; Chlebowski, Colby; Zhang, Aimee; Chorpita, Bruce; Brookman-Frazee, Lauren
Mental health clinicians often report significant challenges when delivering evidence-based interventions in community settings, particularly when unexpected client stressors (or emergent life events) interfere with the therapy process. The current study sought to extend the study of emergent life events to children with autism spectrum disorder by examining the occurrence and impact of emergent life events in the context of a collaborative, caregiver-mediated intervention for reducing challenging behaviors in children with autism spectrum disorder, An Individualized Mental Health Intervention for ASD (AIM HI). Participants included 38 child–clinician dyads enrolled in a community effectiveness trial of An Individualized Mental Health Intervention for ASD. Video recordings of 100 therapy sessions were coded for caregiver-reported emergent life events and clinician adherence to the Individualized Mental Health Intervention for ASD protocol. Results indicated that mild to severe emergent life events were reported in 36% of sessions, and were reported for 58% of children at some point during treatment. Greater number of child comorbid diagnoses and less clinician experience were both significantly associated with a higher number of caregiver-reported emergent life events. There was no significant link between emergent life events and clinician adherence to the Individualized Mental Health Intervention for ASD protocol. Findings offer implications for evidence-based intervention implementation, particularly the importance of incorporating clinician training in addressing complex presentations and crises in the context of evidence-based interventions. Lay abstract: Mental health clinicians often report significant challenges when delivering evidence-based interventions (EBI) in community settings, particularly when unexpected client stressors (or emergent life events; ELEs) interfere with the therapy process. The current study sought to extend the study of ELEs to children with Autism Spectrum Disorder (ASD) by examining the occurrence and impact of ELEs in the context of a collaborative, caregiver-mediated intervention for reducing challenging behaviors in children with ASD. This intervention wasA nI ndividualizedM entalH ealthI ntervention for children with ASD (referred to as AIM HI). Participants included 38 clinicians and child clients who were enrolled in a community effectiveness trial of AIM HI. Video recordings of 100 therapy sessions were coded for caregiver-reported ELEs and also how well clinicians adhered to the AIM HI protocol. Results indicated that mild to severe ELEs were reported in 36% of therapy sessions, and were reported for 58% of children at some point during the intervention. Children who had a greater number of diagnoses (in addition to the autism diagnosis) tended to have more ELEs. In addition, clinicians with less years of experience tended to have sessions with more ELEs. There was no significant link between ELEs and how well clinicians adhered to the AIM HI protocol. Findings offer implications for the implementation of EBI, particularly the importance of incorporating clinician training in addressing complex presentations and crises in the context of EBIs.